A Randomized Controlled Trial of Trypsin to Treat Brown Recluse Spider Bites in Guinea Pigs - Cabaniss, Wyman W.; Bush, Sean; O’Rourke, Dorcas P.; Fletcher, Paul F.; Brewer, Kori L.; Lertpiriyapong, Kvin; Punja, Mohan; Miller, Susan N.; Meggs, William J. (Journal of medical toxicology, 2014)
Brown recluse spider bites result in necrotic skin lesions for which there is no known antidote. Since venom toxins are proteins, a proteolytic enzyme like trypsin might be effective in reducing toxicity. The aim of this study was to conduct a randomized controlled trial of trypsin to treat brown recluse spider bites in guinea pigs. Subjects were 18 female guinea pigs. Anesthesia for injections was inhaled isoflurane. Analgesia was 0.05 mg/kg of buprenorphine twice a day as needed. Intervention was intradermal injection of 30 μg of brown recluse venom (Spider Pharm, Yarnell, AZ). Immediately after envenomation, subjects were randomized to two groups of nine: trypsin 10 μg in 1 mL normal saline and 1 mL of normal saline. The primary outcome was lesion area over a 10-day time period. Statistical analysis was performed with repeated measures ANOVA. Mean lesion area was smaller but not statistically different in the placebo group. Maximum lesion size occurred at day 4 in both groups, when lesion area was 76.1 ± 108.2 mm 2 in the placebo group and 149.7 ± 127.3 mm 2 in the treatment group. P value was 0.15 for placebo vs. treatment. This study did not establish a role for trypsin as a treatment for brown recluse spider bites in a guinea pig model.